Isolation and Structural Elucidation of Flavonoid Compounds from Ciplukan (Physalis angulata L.) Leaf Extract - Cahya, Cucu Arum Dwi; Sinurat, Jhon Patar; Br Turnip, Nur Ulina M.; Br Karo, Reh Malem (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
The exploration and utilization of herbal medicines continue to expand due to the presence of plant-derived secondary metabolites, which have been proven to prevent and treat various diseases with minimal side effects. One plant widely recognized for its medicinal properties is Physalis angulata L. (commonly known as ciplukan). Despite its frequent use in traditional medicine, particularly its leaves, limited studies have focused on the isolation of flavonoid compounds from this part of the plant. The isolation and structural elucidation of these flavonoids are essential to identify the bioactive compounds responsible for the plant's pharmacological effects. This study aimed to isolate and elucidate the chemical structure of flavonoid compounds from P. angulata leaf extract. The powdered leaves were subjected to maceration, solvent partitioning, phytochemical screening, thin-layer chromatography (TLC), and compound isolation using column chromatography. The isolated compounds were then characterized using UV-Visible (UV-Vis) spectroscopy, Fourier-transform infrared spectroscopy (FT-IR), nuclear magnetic resonance (NMR), and mass spectrometry (MS). The flavonoid compound isolated in this study was identified as quercetin (C??H??O?), a member of the flavonol subclass. It exhibited a molecular mass of 302 g/mol and showed maximum absorbance at wavelengths of 372.5 nm and 305.5 nm. Spectroscopic analyses revealed the presence of functional groups including C–O, C=C, C=O, CH, and OH, as well as 10 hydrogen and 15 carbon atoms in the NMR spectra. Based on these data, the isolated compound was confirmed to be 3,3',4',5,7-pentahydroxyflavone, commonly known as quercetin, with the molecular formula C??H??O?.